A afetividade no espaço translíngue emergente em sala de aula de língua com falantes multilíngues - Milozo, Giovana Nicolini (2024)
This research stems from the results of Milozo (2019) work , “Translingual practices in the communication of learners of Portuguese as a foreign language”, which investigated the language practices of five multilingual speakers in a Portuguese language course. Aiming to analyze the dimensions that construct the translingual space, highliting affectivity, this work is justified by the fact that emotions, feelings and affections belong to transcultural and situated domains, which was also perceived in the work of Milozo (2019). The research problem leads to a deeper understanding of the impact of affectivity (Bottura, 2019; Dhokotera, 2019; Dovchin, 2021; García, 2021; Takaki, 2023) on language practices. Under the guidance of the interpretivist paradigm, the methodology used was secondary analysis (Heaton, 2008; Chatfield, 2020), in which previously published data from another research were analyzed. The theoretical apparatus based on translanguaging (Canagarajah, 2011; 2013; Wei, 2011; 2017; 2018; García, 2012; 2015; 2017; 2021; Rocha; Maciel, 2015; Rocha; Megale, 2023), on the linguistic repertoire (Busch, 2012; García; Johnson; Seltzer, 2017; García, 2020) and on decoloniality (Maldonado-Torres; 2000; Quijano; 2002; Walsh, 2012; Mignolo, 2020; Queiroz, 2020; Santos, 2022) is the basis for the analysis. In order to achieve that, a transdisciplinary (Nicolescu, 1999; 2005; 2010) and ecological (Van Lier, 2010; Kramsch; Steffersen, 2017) perspective on the data was necessary, based on theoretical reflections that has knowledge as similar to a rhizome ( Deleuze; Guatari 1995). As a result, the dimensions of the translingual space initially proposed by Wei (2011) were expanded, resulting in five dimensions: physical capacity, cognitive capacity, social capacity, identity aspects and affectivity. Such dimensions become levels of reality (Nicolescu, 2010), in which the individual perspective intertwines with the objective and surrounding reality. Finally, the “critical moments” (Wei, 2011) that emerge in the translingual space characterize the dichotomies of self/other, colonial/decolonial, individual/collective, among others, and are related to the dimension of affectivity, influencing the linguistic repertoire and the process of teaching-learning. Keywords: Translanguaging. Transdisciplinarity. Affectivity. Teaching-Learning.